(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The English suffix -ing, encoding both the gerund and present participle forms, constitutes a morph syntactic marker with multifaceted roles in language structure and use. This paper offers a comprehensive exploration of the cognitive impact of the ing form on language comprehension, focusing on its morph syntactic functions, effects on sentence parsing, semantic interpretation of temporal and aspectual distinctions, and implications for working memory load during real-time processing. Synthesizing findings from psycholinguistics, neurolinguistics, and corpus linguistics, the article demonstrates that the -ing form is a vital cue informing event structure and facilitating predictive parsing mechanisms.